Systems informed positive psychology. Issue 6 (1st November 2020) - Kern, Margaret L.; Williams, Paige; Spong, Cass; Colla, Rachel; Sharma, Kesh; Downie, Andrea; Taylor, Jessica A.; Sharp, Sonia; Siokou, Christine; Oades, Lindsay G.
ABSTRACT: Despite the rapid growth and uptake of the positive psychological perspective by researchers and general audiences, hype regarding the field's potential can lead to exaggerated claims, over-inflated expectations, disillusionment, dismissal, and unintentional harms. To help mature the field, we propose Systems Informed Positive Psychology (SIPP), which explicitly incorporates principles and concepts from the systems sciences into positive psychology theory, methodologies, practices, and discourse to optimize human social systems and the individuals within them. We describe historical underpinnings of SIPP, outline the SIPP perspective, clarify epistemological, political, and ethical assumptions, and highlight implications for research and practice. We suggest that SIPP can generate possibilities for creating sustainable unimagined futures.